INFLAMMATORY RESPONSE IN SOLID ORGAN AND TISSUE RECIPIENT WITH COVID-19 - Lima Verde, Ana Teresa Sobreira; Chaves, Ana Vitória Magalhães; Duarte, Fernando Barroso; Garcia, José Huygens Parente; Fernandes, Paula Frassinetti Castelo Branco Camurça (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2020)
Introduction: The COVID-19 infection is caused by the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-infection, which was first reported in Hubei, Wuhan province, China, in December 2019. There is a concern that immunocompromised patients are at greater risk of morbidity and mortality due to COVID-19 infection, although there is limited data on these patients. Here, we present an evolution of a series of cases of patients with COVID-19 in our service. Patients and methods: This is a retrospective cohort study conducted at the Hospital Universitário Walter Cantídio in Fortaleza-CE, Brazil. All patients hospitalized due to COVID-19 were screened for a history of organ or tissue transplantation, with a total number of 77 patients. Only patients confirmed for COVID-19 were included in the study. The inflammatory response and initial laboratory results, as well as the CALL score, were compared to a cohort of patients with COVID-19 not transplanted at the same time in our clinical ward or intensive care unit (ICU). The clinical course and clinical findings recorded during treatment were extracted from the electronic medical record. A bilateral P <0.05 (5%) was considered significant. Results: The total number of hospitalizations until July 24, 2020 for confirmed cases of COVID-19 was 77 patients. Of the total, 33 (42%) patients needed ICU. Most patients were male (61%). The median age was 62 [95% CI: 54-63] years, 31 (37%) had a previous diagnosis of hypertension, 24 (28%) of type 2 diabetes mellitus (DM-2). The total lethality of our service was 22%. The CALL score of patients admitted to the clinical ward and in the ICU was analyzed, with a higher average observed in the patients admitted in ICU, the average was 9.34 in the patients admitted in the clinical ward and 10.9 in the patients who required ICU. (p = 0.003) . The effect of neutrophil/lymphocyte ratio(NLR) at admission on the need of ICU care was analyzed by ROC curve and AUC and was found to be significant (AUC: 0.708, p = 0.002, 95% CI = 0.593 to 0.823). The number of transplant recipients in our service was 17 patients. The mean age was 56 years and the median was 55 years [95% CI: 45-65 years]. Of this subgroup, 6 patients (35%) required ICU, with no statistical difference when compared to non- transplanted patients (p = 0.443), and only 3 evolved to death (17%), also without statistical difference when compared to the subgroup of non-transplanted patients (p = 0.484). When compared to the sample of non-transplanted patients, lower values were found of the White Blood cells count, neutrophils and ferritin. However, despite lower values of fibrinogen, D-dimer, C-reactive protein (CRP) and lactate dehydrogenase (LDH), there was no statistical difference. Conclusion: It is a new disease, with few data, mainly in the studied population. Our sample was a reduced sample, however it was surprising to see a lower inflammatory tendency, although without statistical significance and with mortality similar to the general population. In addition, it is worth emphasizing the importance shown on the neutrophil / lymphocyte ratio of admission demonstrated by the ROC curve in patients who evolve in need of an ICU care.